Environmental impact evaluation of road pavements using life cycle assessment tool - A. Boonpoke; J. Sriburee; S. Sedpho; T. Prasertsang (Lowland Technology International, 2018)
The acquisition of road construction materials, building processes, rehabilitation, demolition, and disposal of road surfaces adversely impact the environment. In Thailand, the rapid expansion of road transportation networks has raised concerns regarding environmental degradation. Alternative road pavement materials need to be assessed from a life cycle assessment perspective to promote sustainable global development. An environmental impact evaluation was undertaken for two major road types - concrete and asphaltic concrete (AC) pavements - using life cycle impact assessment, with relevant data obtained from related government documents and reports. Results indicated that AC pavement had a higher impact on climate change than concrete pavement, while concrete pavement exhibited a higher impact on terrestrial acidification, human toxicity, metal depletion, and fossil depletion than AC pavement. Building material acquisition and construction contributed the major impact on climate change at 93.2% and 83% for concrete and AC roads, respectively. The mitigation options for reducing the impact of climate change impact were utilization of a mixture of 35 to 50% fly ash with cement instead of cement only in concrete pavement process and implementation of recycling in rehabilitation phase for AC pavement. The findings can be applied to support future decision-making processes for the sustainable development of road construction projects.